Hallerworden — Spatz disease: clinical observation - L. B. Novikova; K. M. Ziultsle; A. P. Akopyan (Лечащий Врач, 2025)
Results. The article describes a clinical observation of a rare hereditary Hallervorden – Spatz disease (pantothenate kinase-associated neurodegeneration or neurodegeneration with iron accumulation in the brain) with an atypical late form in the terminal stage with a debut in the fourth decade of life with a rapidly progressive course and a fatal outcome. The most characteristic signs of the disease in this patient were Parkinsonism syndrome, severe postural instability, pyramidal insufficiency, various types of hyperkinesis, decreased cognitive functions, and depression. When substantiating the diagnosis, we relied on the characteristic clinical picture and typical MRI signs in the form of the tiger's eye symptom (a symmetrical hyperintense zone in the region of the pale globe within a larger hypointense zone). Late cases should be differentiated from such diseases as Parkinson's disease, Lewy body disease, Wilson – Konovalov disease, Fahr disease, Huntington's disease, neuroferritinopathy and others. Due to the current lack of effective treatment methods, the patient received symptomatic treatment, since there is no etiologic and pathogenetic therapy for this disease.Conclusion. The current standard of care is aimed at symptomatic treatment (dopamine agonists or amantadines, anticholinesterase drugs, benzodiazepines, muscle relaxants, botulinum toxin). Surgical treatment methods such as deep brain stimulation, ablative pallidotomy, thalamotomy are also used. It is necessary to increase the awareness of neurologists about the presence of this rare form of neurodegenerative disease with the clinic of parkinsonism due to the presence of other nosological forms of parkinsonism-plus. Early diagnosis of Hallervorden – Spatz disease will allow symptomatic therapy to be prescribed at early stages, corresponding to the various manifestations of the disease, to improve the quality of life of patients and reduce medical and economic costs.